The effect of entrepreneurial inspiration on entrepreneurial intention at Private Universities - Herry Mulyono; Sri Vandayuli Riorini (Jurnal Manajemen dan Pemasaran Jasa, 2023)
Currently, universities face many challenges, specifically, institutions need to be able to produce graduates who are oriented not only towards finding a job but towards creating one, a process known as entrepreneurship, where one of the key elements that significantly influences the emergence, growth, and development of entrepreneurship is the entrepreneurial intention. The purpose of this study is to examine how entrepreneurial inspiration affects entrepreneurial intention, which is mediated by students' perceived behavioral control and personal attitude. A questionnaire with simple random sampling was utilized to gather data from 395 Jambi private university students. On a seven-point Likert-type scale, the respondents were asked to indicate whether they agreed or disagreed with the statements. Data analysis structural equation model. From five hypotheses analyses that were conducted, four hypotheses have positive effects and are significant. Only one hypothesis was rejected, entrepreneurial inspiration on entrepreneurial intention. This hypothesis has a positive impact if it is exclusively mediated by personal attitudes and perceived behavioral control. This study reveals that professionals, motivators, and academics have an important influence in increasing student intentions, which is likely contributing to the improvement of entrepreneurship education in private institutions, particularly in Jambi.